Techno-Economic Analysis of LED Tube Retrofit Applications in Offices - Canol, Bilal; Demirci, Alpaslan; Ayaz, Ramazan (Fırat University, 2023)
In the lighting sector, high energy-efficient LED lighting products are preferred instead of conventional lighting devices to increase energy efficiency. In this study, benefit-cost analyses were conducted by examining retrofit operations both in terms of lighting design and economically by applying different types of T8 LED tubes instead of fluorescent lamps in 4x18W T8 fixtures used in offices. A real office environment was modeled in the DIALux EVO lighting design program, and a total of three different T8 LED tube models with low, medium, and high efficiency were studied in terms of minimum luminance level, average luminance level, uniformity factor, and glare performance. Economically, investment and operating costs, energy savings, and payback periods in retrofit applications of LED tubes with different efficiencies were calculated. As a result, it was observed that medium and high-efficiency LED tubes provided the minimum lighting criteria according to the TS EN 12464-1:2021-09 standard. On the other hand, it was determined that LED tubes with low efficacy factor did not provide the desired lighting performance. Furthermore, high-efficiency LED tubes provided respectively 57% and 24% less energy consumption compared to conventional fluorescent lamps and low-efficiency LED tubes.

Aydınlatma sektöründe enerji verimliliğini arttırmak için konvansiyonel aydınlatma aygıtlarının yerine yüksek enerji verimliliğine sahip LED aydınlatma ürünleri tercih edilmektedir. Bu çalışmada, ofislerde kullanılan 4x18W T8 armatürlerdeki floresan lambalarının yerine, farklı tiplerdeki T8 LED tüpler uygulanarak, retrofit işlemleri hem aydınlatma tasarımı hem de ekonomik açıdan incelenerek fayda–maliyet analizleri yapılmıştır. Gerçek bir ofis ortamı DIALux EVO aydınlatma tasarım programında modellenmiş olup; düşük, orta ve yüksek verimli olmak üzere toplam üç farklı T8 LED tüp modelinin minimum aydınlık düzeyi, ortalama aydınlık düzeyi, düzgünlük faktörü ve kamaşma performansları incelenmiştir. Ekonomik açıdan ise farklı verime sahip LED tüplerin retrofit uygulamalarındaki yatırım ve işletme maliyetleri, enerji tasarrufu ve geri ödeme süreleri hesaplanmıştır. Sonuç olarak; TS EN 12464-1:2021-09 standardına göre minimum aydınlatma kriterlerini orta ve yüksek verimli LED tüplerin sağladığı görülmüştür. Diğer taraftan düşük etkinlik faktörüne sahip LED tüplerin istenilen aydınlatma performansını sağlamadığı belirlenmiştir. Ayrıca yüksek verimli LED tüpler konvansiyonel floresan lambalara ve düşük verimli LED tüplere göre sırasıyla %57 ve %24 daha az enerji tüketimi sağlanmıştır.
Ofislerde LED Tüp Retrofit Uygulamalarının Tekno-Ekonomik Analizi
Keywords: Lighting; Aydınlatma